Majmaea مجمعة Puzzle: An Interactive Strategy to Improve the Arabic Alphabet Knowledge and Sound Recognition of Alive Pupils - Abbas, Amrawda Boone; Aguilar, Rhealyn Lawag; Sayde, Jovel Arellano; Pantao, Jovar G. (Journal of Education Method and Learning Strategy, 2025)
Recognizing the Arabic alphabet and its corresponding sounds can be challenging for Muslim learners in Arabic Language and Islamic Values Education (ALIVE) classes. This study aimed to determine the effectiveness of the Majmaea مجمعة Puzzle, an interactive strategy designed to enhance Arabic alphabet knowledge and sound recognition among Grade I to Grade III learners in the Arabic Literacy and Values Education program at NASA Elementary School during the academic year 2022-2023. Employing a single-subject experimental design, 31 selected pupils participated in the study, with assessments conducted through pre-tests and post-tests. Statistical analyses, including descriptive statistics and t-tests for dependent samples, were utilized to the data. The findings indicated that before the implementation of Majmaea Puzzle, learners exhibited a very low level of Arabic knowledge and sound recognition, with a mean score of 35%. Contributing factors included difficulties in phonological awareness and limited engagement with traditional teaching methods. Following the intervention, there was a significant improvement, with a post-test mean score of 81%, demonstrating that the interactive and contextualized nature of the Majmaea Puzzle effectively facilitated learning. The results suggest that incorporating interactive strategies like the Majmaea Puzzle can significantly improve the Arabic literacy of young learners. Hence, it is recommended that educators implement this approach to foster better engagement and proficiency in Arabic language skills.